Clinicoaudiological evaluation of hearing improvement in patients with sensorineural hearing loss using intratympanic platelet rich plasma versus steroid injection - Tom, Stephy Maria; Sachdeva, Kavita; Kabade, Mayur V.; Shukla, Amrita; Raj, Lakshmy V. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: SNHL is a heterogenous disorder, which can arise due to damage to pathway for sound impulses from the hair cells of inner ear to auditory nerve. This study is to evaluate and compare the effect of intratympanic instillation of PRP in patients having sensorineural hearing loss with steroid therapy. Methods: A prospective observational study carried out in the department of ENT, NSCB medical college Jabalpur. The cases were selected who presented with sensorineural hearing loss and mixed hearing loss with intact TM. Total of 54 cases were enrolled in the study from 1March, 2020 to 31 August 2021.Preoperative PTA was recorded. 0.5 ml of intratympanic platelet rich plasma and 0.5 ml of steroid dexamethasone administered. Postoperative PTA was done after 15 days of intratympanic injection and results recorded. Results: In our study the mean age of the participants was 40.4 years. Bilateral and gradual hearing loss were common in the present study. The improvement from baseline to follow up period was higher in PRP group compared to DEXA group. It is statistically significant (p=0.001). The improvement in hearing loss is decreasing with the increase in age. The study revealed that hearing improvement with PRP is better than steroid. Conclusions: The study concluded that the hearing improvement was more with single injection of PRP than dexamethasone.